Assessment of the vegetation and turf management value of horse pastures with different uses in the horse park near Sukoró - Molnár, Barna; Rednágel, Csongor; Saláta-Falusi, Eszter; Balogh, Petra; Bajnok, Márta (Animal welfare, Ethology and Housing Systems (AWETH), 2023)
The study was carried out in Sukoro, on the grasslands of the Sukoro Equestrian Centre in May 2023. The study presents the natural condition and the economic value of grasslands with different uses. In parallel to the coenological survey, grassland management studies were also carried out. The forage quality was assessed using the Balázs method and the Klapp method. Five sample plots in three units were surveyed. Sample plot I was degraded grassland, horse pasture, and sample plot II was a French meadow used as a mowing field. Sample plot III was a salt grassland used as a horse pasture and sample plot IV was a marsh prairie, also used as a mowing field. Sample plot V was a siliceous rocky grassland grazed by horses. Of the plots studied, sample plots II and IV were the best based on forage quality analysis. In sample plot I, where the vegetation was more degraded, the soil was also poorer, which affected the economic value of the grassland and here species of poorer quality from a grassland management point of view became predominant. In III, the saline grassland, on poorer soils, was also dominated by species of lower grassland management value (e.g. Festuca pseudovina). In sample area V, high proportions of thorny and toxic (e.g. Euphorbia spp.) plant species, which impair forage quality, were present, a remnant of past overgrazing.